Sexual Child Abuse: Understanding and Representing Clinical Practices Within Mental Health Practices [Abuso Sexual Infantil (Asi): Comprensiones y Representaciones Clínicas Desde Las Prácticas de Salud Mental] - Magana-Frade, I; Ramirez-Munoz, C (Sociedad Chilena de Psicologia Clinica, 2014)
Relevant results include: excessive tendencies to treat the matter as a juridical case and as pathology; the need for interdisciplinary work; the difficulty of repairing and preventing; the presence of discontent and unease in professionals related to their work; social relations in the presence of SCA of an authoritarian type; and the devastating psychic damage, both direct and indirect, in its victims.This study investigates Sexual Child Abuse (SCA) in its clinical context, including its representational, conceptual, and cultural expressions. Working with professionals of institutions, following an analytic yet understanding method, this study traces their approaches at the clinical level as well as intervention policies. Methodologically, the investigation is observational, analytic, and longitudinal, and qualitative design study, including two temporal cohorts (2005-2006 and 2011-2012). These methods were chosen to acquire better knowledge regarding the strategies used in clinics. © 2014 by Sociedad Chilena de Psicología Clínica.